Listeria Occurrence in Poultry Flocks: Detection and Potential Implications - Rothrock, Michael J.; Davis, Morgan L.; Locatelli, Aude; Bodie, Aaron; McIntosh, Tori G.; Donaldson, Janet R.; Ricke, Steven C. (Frontiers in Veterinary Science, 2017)
Foodborne pathogens such as Salmonella, Campylobacter, Escherichia coli, and Listeria are a major concern within the food industry due to their pathogenic potential to cause infection. Of these, Listeria monocytogenes, possesses a high mortality rate (approximately20%) and is considered one of the most dangerous foodborne pathogens. Although the usual reservoirs for Listeria transmission have been extensively studied, little is known about the relationship between Listeria and live poultry production. Sporadic and isolated cases of listeriosis have been attributed to poultry production and Listeria spp. have been isolated from all stages of poultry production and processing. Farm studies suggest that live birds may be an important vector and contributor to contamination of the processing environment and transmission of Listeria to consumers. Therefore, the purpose of this review is to highlight the occurrence, incidence, and potential systemic interactions of Listeria spp. with poultry.